Intersectional Promises: How Well did the Canadian National Action Plan to End Gender-Based Violence Integrate an Intersectional Approach? - Kochkina, Olesya (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
It took more than ten years of feminist advocacy for the Canadian government to adopt the National Action Plan (NAP) to End Gender-Based Violence (GBV) on November 9, 2022. This study is among the first to trace the development of and critique the NAP. Specifically, I interrogate how well is the NAP grounded in an intersectional approach. Using the adjusted Intersectionality-Based Policy Analysis (IBPA) and qualitative content analysis as research methods, I argue that the recently adopted NAP is premised on a deflated definition of intersectionality and lacks attention to the role of existing policies in reproducing social inequalities. The NAP fails to centre the voices of those most affected and to demonstrate an in-depth understanding of systemic causes and effects of GBV resulting in different intersectional needs of various at-risk groups. As a consequence, the NAP provides symbolically intersectional solutions that are unlikely to be effective in addressing GBV. In addition, the NAP relies on non-intersectional data for progress assessment, and it is without built-in mechanisms for meaningful engagement of the most affected groups. With such a design, the current NAP will not be able to achieve the stated vision of a Canada free from GBV.